Usefulness of Cyclin D1/Podoplanin Dual Immunohistochemical Stain to Differentiate Malignant Mesothelioma From Reactive Mesothelial Proliferations. Issue 2 (14th March 2022) - Pillappa, Raghavendra; Wiles, Austin; Sayeed, Sadia; Robila, Valentina
Abstract: Objectives: To examine the potential of cyclin D1/podoplanin dual immunohistochemical stain to differentiate malignant mesothelioma from reactive mesothelial proliferations. Methods: Cyclin D1/podoplanin dual immunohistochemistry was performed on 34 surgical cases of reactive mesothelial proliferations, malignant mesothelioma, and nonmesothelioma malignancies. Results: All 15 reactive mesothelial proliferations demonstrated less than 50% cyclin D1 staining with variable to diffuse podoplanin staining. In 6 (60%) of 10 cases of epithelioid malignant mesothelioma, the dual stain supported the diagnosis. Less than 50% cyclin D1 staining was noted in the remaining four cases, including small biopsy specimens or cases with focal papillary architecture. The five cases of sarcomatoid/desmoplastic/biphasic mesothelioma showed more than 50% cyclin D1 staining with focal to absent podoplanin staining. Well-differentiated papillary mesothelioma appears to demonstrate less than 25% cyclin D1 staining. Conclusions: The cyclin D1/podoplanin dual stain is reliable and may be used to aid in differentiation of benign mesothelial proliferations from malignant tumors. In addition, histologic features and other ancillary testing may support the classification of cases with an inconclusive cyclin D1/podoplanin staining.